The role of Job Satisfaction as a mediator of the relationship between Cognitive Flexibility, Digital Literacy and Job Performance of Non-ASN Employees in Work Units in charge of Personnel, Planning and Finance within the Regional Secretariat of Serang City - Putro, Eko; Basrowi; Permana, Angrian (Center of Language and Cultural Studies, 2024)
In the rapidly developing digital era, employee performance is the main key to the effectiveness and efficiency of public services, especially in the Regional Secretariat of a region. Lack of Cognitive Flexibility and Digital Literacy among non-ASN employees at the Serang City Regional Secretariat, this is a significant challenge. Inability to adapt to technological changes and lack of understanding of digital technology can affect their performance. This obstacle needs to be overcome with intensive training efforts and competency improvement. This research adopted the structural equation modeling partial least squares (SEM-PLS) analysis method for a sample of 125 non-ASN employee respondents at the Serang City Regional Secretariat through the application of the Stratified Random Sampling technique. Exogenous variables in this research includeCognitive Flexibility by utilizing 10 indicators, as wellDigital Literacy using 11 indicators.Job Satisfaction acts as an intervening variable with 11 indicators, whereasJob Performance employee is an endogenous variable with 15 indicators. A total of 7 hypotheses were tested in the framework of this research. The results of the Outer Model evaluation showed that of the total of 47 indicators tested, 11 indicators were found to be invalid because they had a loading factor value below 0.70, while the remaining 36 indicators were proven to be valid. The results of hypothesis testing revealed that of the 7 hypotheses proposed, 6 hypotheses were successfully accepted while 1 other hypothesis was rejected. Thus, this research provides an in-depth understanding of the factors that influence the performance of non-ASN employees at the Serang City Regional Secretariat, and their implications for increasing the effectiveness and efficiency of public services in the increasingly developing digital era.